2010
DOI: 10.1111/j.1749-4486.2010.02164.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Squamous cell carcinoma of the oral tongue in patients younger than 30 years: clinicopathologic features and outcome

Abstract: In this study, patients younger than 30 years of age presented with advanced tumour stages and with a different failure pattern compared to the older age group. This may be attributable to age-related biologic behaviour or delayed cancer diagnosis. Differences in disease free survival and overall survival could not be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
4
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 22 publications
13
79
4
6
Order By: Relevance
“…As for sample size, the number of participants ranged from 10 to 2,223 young subjects, as described in Table 1. Age distribution of patients varied: individuals considered young were those aged 18-39 years (7,8,10,11) (23.5%), < 30 years (13,20) (3,6,8,9,(11)(12)(13)(14)(16)(17)(18)(19)(20)(21) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As for sample size, the number of participants ranged from 10 to 2,223 young subjects, as described in Table 1. Age distribution of patients varied: individuals considered young were those aged 18-39 years (7,8,10,11) (23.5%), < 30 years (13,20) (3,6,8,9,(11)(12)(13)(14)(16)(17)(18)(19)(20)(21) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 studies that associated SCC to the oral cavity, seven used only lesions in the tongue (3,6,8,12,13,15,20) as inclusion criteria; nine included other locations, of which six identified the tongue as the site of highest incidence (7, 9-11, 14, 16) , and just two observed predominance on the floor of mouth (18,21) . Concerning the relationship with harmful habits, nine investigations demonstrated association between tobacco and/or alcohol use and OSCC, of which six presented positive association (7,10,11,16,18,19) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence rate of HNSCC has reached 0.4-3.6% in patients younger than 40 years which has drawn physicians' attention to the changing face of the disease (Llewellyn et al, 2001). On the other hand, recent studies have revealed differences of the risk factors and prognosis of HNSCC, in patients younger than 40 and the older patients, although controversy still exists regarding disease outcomes in young and old patients: some authors report a worse prognosis of the disease in the young compared to the old (Mallet et al, 2009;Kaminagakura et al, 2010;Soudry et al, 2010;Bachar et al, 2011;Kostrzewska-Poczekaj et al, 2012) while other studies have not found a significant clinical difference, or even a more favorable prognosis in younger patients (Luna-Ortiz et al, 2011). In fact, even if the tumors are histologically more mature and less malignant in younger patients compared to older ones, they are usually more advanced clinically at the time of diagnosis due to late referral of young patients to physicians (Shiboski et al, 2005;Sink et al, 2011).…”
Section: Introductionmentioning
confidence: 99%